ANALISIS PERKEMBANGAN NERACA PERDAGANGAN INDONESIA SEBELUM DAN SESUDAH PERANG DAGANG AMERIKA SERIKAT-CHINA - Rahayu, Sri Endang (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The United States and China are heading for a trade war. The two countries made protection policies to prevent the entry of goods produced by the opposing party. The trade war caused by the economic policies of the two countries had an impact on the global economy, including Indonesia. The current account balance and trade balance in Indonesia experienced a deficit following the trade war between the United States and China. The United States-China trade war negatively affected Indonesia's financial sector. Trade tensions between the United States and China have had a negative impact on the global economy, especially the Indonesian economy, by reducing commodity exports. Indonesia's trade balance before the United States-China trade war in 2015 to 2017 experienced a surplus where exports were still large compared to imports. Meanwhile, after the United States trade war in 2018 to 2019, Indonesia's trade balance experienced a deficit in which imports of goods were greater than imports. In the January-October 2020 period, Indonesia's trade balance returned.